KONSEP PERANCANGAN TAMAN REKREASI DAN OLAHRAGA DI KELURAHAN BALEARJOSARI KOTA MALANG - Angwarmas, Faustinus; Setyabudi, Irawan (Aksen : Journal of Design and Creative Industry, 2020)
Open space is a space that is used for joint activities in the open air, while the kinds are green open spacesand built-in open spaces (public and private). A space will have meaning if there is human activity in it andnot only as an abandoned space. In this study, an open space design was carried out, with changes in theland use function of agricultural land. Park area designed for 3,100 m2. After discussing with local residents,sports facilities are needed in Balearjosari Village. The reason for choosing the location is that the surroundingconditions are still natural and in the countryside so that it attracts visitors to the area. Another facility neededis a recreation area in the form of a children’s playground. This study aims to create the concept of Balearjosaripark as recreation and sport with a landscape architecture approach. The research method used the designmethod as a development of the theory of Gold (1988) and Hakim (2012), namely by the stages of surveyand interview, analysis and synthesis, ideas and continued with the design concept. The results in this studyare in the form of various concepts consisting of basic concepts, form concepts, space concepts, circulationconcepts, activity and facilities concepts, vegetation concepts, and material concepts. Its novelty value issolving problems according to the needs of the park in that location, making it different from other areas. Theconclusion is that the solutions offered by landscape architects can provide an overview to the community inthe form of recreational and educational park design concepts, according to community needs. Keywords: Concept, Parks, Recreation and Educationt, Balearjosari